A Review of CSR as Practised by Nigerian Banks in The Face of Globalisation - Adelagun, Oyereyi Adetoun (2009)
In recent years CSR has become a fundamental business practice and has gained much attention from chief executives, chairmen, boards of directors and executive management teams of larger international companies. They understand that a strong CSR program is an essential element in achieving good business practices and effective leadership. Companies have determined that their impact on the economic, social and environmental landscape directly affects their relationships with stakeholders, in particular investors, employees, customers, business partners, governments and communities.